Childhood Disability Rates in Ukraine over the Period 2010-2014 - S.R. Tolmachîva; T.V. Peresypkina (Zaslavsky O.Yu., 2016)
The problem of primary and general childhood disability in the country is a topical medical and social problem that requires systematic monitoring and multiple solutions. In recent years the number of children with special need is growing. The structure of childhood disability since 1993 has not changed: congenital abnormalities lead, then nervous system diseases and mental and behavior disturbances follow.